An Intelligent Controller Design Approach for MIMO Coupled Tank System - Mohd Hafiz Jali; Ahmad Firdaus Azhar; Rozaimi Ghazali; Chong Chee Soon (IAES International Journal of Robotics and Automation (IJRA), 2018)
Nowadays, versatilities of controllers have been developed to control the Coupled Tank System (CTS) such as proportional, integral, derivative (PID), fuzzy, fuzzy PID and neuro network. This paper focused on the control of the pump flow rate, in and out of the tank against the cross-sectional area of the CTS’s tank. The main objective of this paper is to design a CTS by using MATLAB since the Fuzzy Logic Controller (FLC) is widely utilized in the control of engineering applications in the industrial. Therefore, the FLC will be utilized to control and improve the performance of the CTS. The conventional PID controller will be applied, which reacts as a benchmark in the performance of the FLC. Parameters such as steady state error, settling time, and maximum overshoot will be part of the simulation results. As a result of the dynamic response executed in the closed-loop environment, it can be concluded that the FLC is capable of performing better than the conventional PID controller.